2022
DOI: 10.1007/s10823-022-09459-x
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in Myanmar’s older population: A mixed-methods investigation

Abstract: Objectives Little is known about loneliness in lower- and middle-income countries. This study investigates loneliness in the older population of Myanmar using a mixed-methods approach. Methods To identify predictors of loneliness, hierarchical regression models were used to analyze data from the Myanmar Aging Survey 2012 (N = 3,618, 57% women). In a mixed-methods sequential explanatory design, quantitative data were integrated with qualitative data from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…The results of the multiple regression analysis showed that ST had significant associations with UCLA for educational level, subjective economic status, subjective health status, and GSES, while MT had significant associations with UCLA for subjective economic status, subjective health status, and GSES. Studies conducted before the coronavirus pandemic revealed that health problems (multiple diseases, poor health) [55,56], subjective health status [35], low income [35,55], and education (years) [34] were associated with loneliness, which is consistent with the results of the present study. Therefore, variables such as educational level, subjective economic status, and subjective health status may be important variables for predicting loneliness in ST and MT individuals during the coronavirus pandemic.…”
Section: Comparison Of Ucla-related Factors By Household Typesupporting
confidence: 92%
“…The results of the multiple regression analysis showed that ST had significant associations with UCLA for educational level, subjective economic status, subjective health status, and GSES, while MT had significant associations with UCLA for subjective economic status, subjective health status, and GSES. Studies conducted before the coronavirus pandemic revealed that health problems (multiple diseases, poor health) [55,56], subjective health status [35], low income [35,55], and education (years) [34] were associated with loneliness, which is consistent with the results of the present study. Therefore, variables such as educational level, subjective economic status, and subjective health status may be important variables for predicting loneliness in ST and MT individuals during the coronavirus pandemic.…”
Section: Comparison Of Ucla-related Factors By Household Typesupporting
confidence: 92%